Optimization structure database of complex systems - M. Korneev, A; K. Pogodaev, A; S. Abdullakh, L; V. Salfetnikov, M (International Journal of Engineering and Technology, 2018)
In the article such ways of optimization of the structure of a database of complex structured objects that allow simplifying the scheme of an information system. As a result, the response time of the information system to the user's request is reduced, and it becomes possible to more effectively manage and monitor the progress of ongoing processes. A formalized model of the relational expression is developed, a model of the corresponding equivalent transformation of the chosen relational expression is created, a formal description of the developed algorithm for optimizing the queries is presented.Â Â
Keywords: Optimization Structure; Database; Information; System; Modeling Processes.